Otimização dos ensaios de triagem de compostos tripanocidas - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
Few drugs are available against Chagas disease, caused by protozoa Trypanosoma cruzi. Most of these drugs cause severe side effects and there is no data on a drug with a 100% cure rate. Screening of new anti-T. cruzi compounds is initiated with in vitro tests against epimastigotes and intracellular amastigotes. Against amastigote forms, clinically relevant because are present in mammalian host, trypanocidal effect is mainly evaluated by microscopic count of residual parasites. Although reproducible, this technique is time-consuming and depends on experience of the microscopist. This work aims to develop a screening method for trypanocidal compounds through detection of fluorescence emitted by TcGFP. Epimastigotes of Y strain (108 parasites/ml) grown in LIT+10% FBS medium were transfected with plasmid pROCKGFPNeo and selected by serial dilution and G418 resistance antibiotic. After selection, epimastigotes showed homogeneous and stable GFP expression. GFP expression also remained stable in both trypomastigotes and intracellular amastigotes. Transfection did not affect the in vitro replication profile of epimastigotes, nor their susceptibility to benzonidazole. Furthermore, the strain was able to infect and replicate in Vero E6 cells. Through fluorimetry, there was a direct correlation between fluorescence intensity and concentration of epimastigote (R2=0.9986) and intracellular amastigotes (R2=0.9559) of TcGFP parasites. Aiming to validate the fluorimetric technique for trypanocidal compound screening, epimastigotes and cells containing intracellular TcGFP amastigotes were incubated with different concentrations of benzonidazole for 48 and 24 hours, respectively. The results showed that anti- epimastigotes tests were viable just to the compounds that cause lysis of the parasites, due to the fluorescence detecting of GFP retained in non-lysed unviable parasites. For intracellular amastigote forms, the proposed fluorimetric method can be applied, replacing the time-consuming microscopic count.
Keywords: Atividade tripanocida; Trypanosoma cruzi; GFP; Otimização; Trypanocidal activity; Trypanosoma cruzi; GFP; Optimization; CNPQ::CIENCIAS BIOLOGICAS